(untitled) (Security Dialogues, 2024)
The 2022 Summit of Heads of State and Government of the Alliance was held in Madrid in June 28-30. The Summit took place in the context of a conventional threat to the security of the Euro – Atlantic area as well as in a time of war on the European soil. NATO leaders discussed strategically important issues facing the Alliance, endorsed the New Concept of the Alliance, and made a series of key decisions that will have a direct impact on the future of the Alliance. Namely, at the Summit, the leaders agreed on fundamental shifts regarding the deterrence and defense doctrine, on the challenges and threats from the South related to the fight against terrorism and the 360-degree approach to deterrence and defense. They agreed to invest more in NATO with the intention to increase common funding for the Alliance’s adaptation to growing challenges such as climate change, and invited Sweden and Finland to join the Alliance. The Leaders agreed on long-term support measures for Ukraine by strengthening the Comprehensive Assistance Package and reaffirmed common interests and shared values. The Summit has set NATO’s new strategic direction for the future, ensuring that the Alliance will continue to adapt in a changing world in order, at any moment to be ready to provide protection to over one billion people living within its borders.